Energy Aware Dynamic Provisioning for Heterogeneous Data Centers - Villebonnet, Violaine; Costa, Georges Da; Lefevre, Laurent; Pierson, Jean-Marc; Stolf, Patricia (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2016: Anais do XXVIII International Symposium on Computer Architecture and High Performance Computing, 2016)
The huge amount of energy consumed by data centers represents a limiting factor in their operation. Many of these infrastructures are over-provisioned, thus a significant portion of this energy is consumed by inactive servers staying powered on even if the load is low. Although servers have become more energy-efficient over time, their idle power consumption remains still high. To tackle this issue, we consider a data center with an heterogeneous infrastructure composed of different machine types - from low power processors to classical powerful servers - in order to enhance its energy proportionality. We develop a dynamic provisioning algorithm which takes into account the various characteristics of the architectures composing the infrastructure: their performance, energy consumption and on/off reactivity. Based on future load information, it makes intelligent decisions of resource reconfiguration that impact the infrastructure at multiple terms. Our algorithm is reactive to load evolutions and is able to respect a perfect Quality of Service (QoS) while being energy-efficient. We evaluate our original approach with profiling data from real hardware and the experiments show that our dynamic provisioning brings significant energy savings compared to classical data centers operation.